POTENCIALIDADES Y APLICACIONES DE LAS INTELIGENCIAS MÚLTIPLES - Stecconi, Cristina (European Scientific Journal, ESJ, 2015)
Traditionally and even today, most educational institutions at all levels tends to value exclusively or at least predominantly, the kinds of intelligence that Gardner (1983) called Logical/Mathematical and Verbal/Linguistic. They are required especially in careers like engineering, systems, or law. People who do not excel in these areas tend to be discriminated, and this could lower their self esteem and performance. However, other carreers primarily involves additional skills, such as the case of Psychology, Graphic Design, or Physical Activity and Sport. In this sense, Gardner (1983) proposed the existence of at least 5 other types of intelligence: Intrapersonal, Interpersonal, Visual/Spatial, Bodily/Kinesthetic, and Musical/Rhythmic. In turn, each type of Intelligence is decomposable into a number of sub-intelligences that describe different aspects of it. According to MacÃas (2002), "This new view of intelligence vindicates the human condition in relation to its multiple capabilities of cognition and education, and in generatings new pedagogical and institutional practices. Finally, the value of the cultural environment for the development of human intellect is stressed" (p.27). In addition, he continues: "Every intelligence expresses a capability that operates according to its own procedures, systems and rules, and has its own biological basis" (p.32)